Entrepreneurship education and undergraduate students' self- and paid-employment intentions: A conceptual framework. Issue 1 (14th January 2019) - Otache, Innocent
Abstract : Purpose: The purpose of this paper is to conceptually explore the relationship between Entrepreneurship Education (EE) and undergraduate students' self- and paid-employment intentions. Specifically, the paper aims to examine the effect of paid-employment intention on the relationship between EE and self-employment intention. Design/methodology/approach: This paper reviewed extensively related literature on EE, entrepreneurial intentions and the theory of planned behaviour (TPB). The detailed literature review undertaken formed the basis for the development of the conceptual framework. Findings: It is found that undergraduate students have two opposing employment intentions within them, namely, self- and paid-employment intentions. The two employment intentions interact and have a tendency to dominate each other, and consequently lead to different employment behaviours. The dominant employment intention determines whether a graduate will exhibit self- or paid-employment behaviour. This confirms that graduates are faced with two career paths or choices, namely, self- and paid-employment. Research limitations/implications: It is not an empirical paper. Thus, the conceptual framework needs to be further empirically tested. More specifically, the proposition that undergraduate students' paid-employment intentions moderate the impact of EE on their self-employment intentions needs to be empirically validated. Practical implications: This paper provides some insightful and practical implications for the government and the policymakers in the education sector, particularly in tackling the menace of graduate unemployment and its associated problems. It provides an insight into the problem of graduate unemployment. The government and the policymakers should initiate enlightenment programmes that will reorient undergraduate students away from having the mentality of securing paid-jobs after graduation. Equally, undergraduate students should be enlightened about the difficulties in securing paid-jobs and the benefits of being a self-employed graduate. Originality/value: It is the first to explore the moderating effect of undergraduate students' paid-employment intentions on the relationship between EE and their self-employment intentions. Therefore, it makes a valuable contribution to the existing literature on EE and entrepreneurial intentions. It further strengthens the TPB by applying it to explain how undergraduate students' paid-employment intentions could neutralise the impact of EE on their self-employment intentions.